Long-term follow-up of HIV-1-infected adults who received the F4/AS01(B) HIV-1 vaccine candidate in two randomised controlled trials - Harrer, Thomas; Dinges, Warren; Roman, Francois (Vaccine, 2018)
This Phase I/II open, long-term follow-up study was conducted in antiretroviral therapy (ART)-naive (N = 212) and ART-treated (N = 19) human immunodeficiency virus 1 (HIV-1)-infected adults, who received an HIV-1 investigational vaccine (F4/AS01(B)) or placebo in two previous studies (NCT00814762 and NCT01218113). After a minimum of two years and a maximum of four years of follow-up postvaccination per patient, no significant differences were observed between F4/AS01(B) and placebo groups in terms of viral load, CD4(+) T-cell count and incidence of specific clinical events. Vaccine-induced polyfunctional CD4(+) T-cells persisted up to study end and no relevant vaccine-related safety events were reported in F4/AS01(B) groups. (C) 2018 The Authors. Published by Elsevier Ltd.
EVALuna2:213268